2020
DOI: 10.3389/fbioe.2020.00202
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional Injection of Bone Marrow Aspirate Concentrate for the Treatment of Osteonecrosis of the Knee Secondary to Systemic Lupus Erythematosus: A Case Report

Abstract: Case: An 18-year-old female patient with Systemic Lupus Erythematosus (SLE) and corticosteroid-associated extensive bilateral symptomatic knee Osteonecrosis (ON) (Ficat IV), treated with sequential intralesional injections of autologous bone marrow aspirate concentrate (BMAC) under ultrasound guidance. At 3 months, pain was almost absent (VAS) and KOOS/WOMAC showed significant improvement sustained up to 24 months. At 12 months MRI indicated bone maturation, significantly reduced BM edema and subchondral fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Biological modalities like stem cell therapy, on the other hand, were shown to harbor a regenerative potential in several pre-clinical ( 13 , 14 ) and clinical studies ( 18 , 23 , 38 ). Although BMAC administration was demonstrated to be clinically safe and promising for several orthopedic conditions including IDD ( 18 , 21 , 30 , 39 ), no studies addressed or supported its use for facetogenic chronic LBP. In fact, all studies targeting facet joint-mediated pain were conducted using platelet rich plasma or prolotherapy ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biological modalities like stem cell therapy, on the other hand, were shown to harbor a regenerative potential in several pre-clinical ( 13 , 14 ) and clinical studies ( 18 , 23 , 38 ). Although BMAC administration was demonstrated to be clinically safe and promising for several orthopedic conditions including IDD ( 18 , 21 , 30 , 39 ), no studies addressed or supported its use for facetogenic chronic LBP. In fact, all studies targeting facet joint-mediated pain were conducted using platelet rich plasma or prolotherapy ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under sterile conditions, autologous BMAC was prepared as previously described ( 30 ). Briefly, the Posterior Superior Iliac Spine was marked with ultrasound guidance for bone marrow aspiration, and 2% lidocaine was injected into the soft tissue and periosteum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the proposed mechanism of action for therapeutic efficacy is the use of bone marrow harvested and concentrated from a healthier location as a method of repopulating MSCs in the diseased ON lesions. In addition, one case report has discussed an 18-year-old female with steroid-induced bilateral knee ON (Ficat IV) treated with five separate subchondral injections using BMC with the resolution of pain in three months, improvement of bone marrow edema, and bone maturation on repeat MRI at 12 months, and significant improvement in Knee Injury and Osteoarthritis Outcome Score (KOOS) and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores at 24 months [15]. Hernigou et al also demonstrated the ability of intraosseous implantation of BMCs to significantly postpone arthroplasty in patients with knee osteoarthritis [10].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical interventions include joint-preserving surgery, total knee arthroplasty (TKA), unilateral knee arthroplasty (UKA), core decompression, and high tibial osteotomy [2]. Since the late 1990s, investigations of biologic materials, including autologous bone marrow concentrate (BMC) and platelet-rich plasma (PRP), have shown promise in treating a variety of musculoskeletal pathologies [10][11][12][13][14][15]. For bone marrow lesions and AVN in particular, the proposed therapeutic mechanism of action involves the repopulation of the subchondral microenvironment with healthier mesenchymal signaling cells (MSCs) transferred via concentrated bone marrow aspirated from a different anatomic location [14].…”
Section: Introductionmentioning
confidence: 99%